Improvement of clinical course of liver cirrhosis due to chronic hepatitis C after sucessful treatment with direct acting antivirals - Cedrón-Cheng, Hugo (2021)
Direct-acting antivirals are new drugs, highly effective and safe against chronic hepatitis C. However, despite of hepatitis C erradication in patients with decompensated liver cirrhosis, their effect in improving the clinical course, reducing liver-related complications and the risk of developing portal hypertension and hepatocellular carcinoma is still controversial. We present two patients with decompensated liver cirrhosis Child B due to hepatitis C who received treatment with direct-acting antiviral drugs. After treatment, and with the confirmation of undetectable viral load – sustained viral response – both patients showed significant improvement in the clinical course of liver cirrhosis – Child A – and a decrease in the amount of liver fibrosis measured with non invasive methods.